First‐Principle Studies of the Enhancement of Rashba Effect in Ultrathin GeTe Films by Structural Engineering. Issue 6 (14th April 2022) - Yao, Yang; Huang, Hong‐Fei; Dong, Yao‐Jun; Gu, Han; Zhong, Jia‐Lin; Hao, Xiang; Wu, Yin‐Zhong
Abstract: It is well known that electronic energy bands are split by spin‐orbit coupling in a system that lacks inversion center, and the bulk Rashba effect in ferroelectric semiconductor GeTe has attracted intensive attention due to its giant Rashba coefficient. However, the Rashba effect in GeTe film will disappear below a critical thickness due to the occurrence of centrosymmetric structure with decreasing thickness. In this paper, GeTe/In 2 Se 3 $_2\text{Se}_3$ heterostructures are investigated by means of first‐principle calculations, and it is found that the Rashba effect not only can be revived for the nonpolar‐GeTe film, but also can be enhanced for the ultrathin polar‐GeTe film. The variation of the bias field within the GeTe film in the heterostructure in contrast with that within the isolated GeTe film may be employed to explain the remarkable improvement of Rashba effect and the spin textures around the spin‐split band. Furthermore, the influence of the In 2 Se 3 $_2\text{Se}_3$ polarization on the Rashba coefficient is also discussed. With the increasing demands of device miniaturization, the authors hope that the method of constructing heterostructure may be an alternative route to enable large Rashba effect surviving down to the ultrathin film limit. Abstract : By introducing a ferroelectric In 2 Se 3 $_2\text{Se}_3$ substrate, the Rashba effect not only can be created in nonpolar GeTe film, but can also be enhanced in polar GeTe film. The authors hope that heterostructure engineering may be an effective way to enable a large Rashba effect surviving down to the ultrathin film limit.